VERTICAL PROFILES OF TOTAL ORGANIC CARBON AND POLAR ORGANIC COMPOUNDS IN THE ICE CORE FROM SITE-J, GREENLAND - カワムラ, キミタカ; ヨコヤマ, カズヒサ; フジイ, ヨシユキ; KAWAMURA, Kimitaka; YOKOYAMA, Kazuhisa; FUJII, Yoshiyuki (National Institute of Polar Research, 1992)
P(論文) Forty two sections from a 206m long ice core (ca. 450yr old at the bottom) were studied for total organic carbon (TOC) content and distributions of polar organic compounds including C_2-C_<10> dicarboxylic acids, C_2-C_4 oxocarboxylic acids, C_2-C_3 aldehydes and C_<14>-C_<18> fatty acids. TOC contents in the ice core samples ranged from 0.7 to 5.7ppm (μg/g-ice) : however, no clear trend was observed in the vertical profile. Concentration ranges of total diacids, oxoacids, aldehydes and fatty acids were 3.1-32.4,0.1-2.6,0.09-1.7 and 0.01-11.1 ng/g-ice, respectively. Vertical profiles of diacids and fatty acids showed peaks at 6.9 and 32-35m depths. departmental bulletin paper